Dracaena trifasciata (Prain) Mabb leaf extract protects MIN6 pancreas-derived beta cells against the diabetic toxin streptozotocin: role of the NF-κB pathway - Hoornenborg, Christiaan Warner; Qomariyah, Nur; González-Ponce, Herson Antonio; Van Beek, André Petrus; Moshage, Han; Van Dijk, Gertjan (Frontiers in Pharmacology, 2025)
BackgroundDracaena trifasciata (Prain) Mabb. [Asparagaceae; also known as Sansevieria trifasciata Prain (ST)] may have health-promoting activities, including resolution of diabetes mellitus (DM). This in vitro study evaluated whether and how a leaf extract of ST could directly protect pancreas-derived MIN6 cells against the diabetogenic toxin streptozotocin (STZ).MethodsComposition of the ST extract (by 100% methanol) was investigated using high resolution mass spectrometry, which revealed several compounds with beneficial bioactive efficacy. MIN6 cells were exposed to 50% lethal dose of STZ, with or without ST extract. Cell viability was assessed using the MTT method. Inflammatory activity of ST extract was assessed in MIN6 cells and macrophage-like RAW cells, and addition of TNF-α to combinations of ST and STZ were tested on MIN6 cell viability. The role of the NF-κB pathway in effects of STZ and ST were investigated using the proteosome inhibitor MG132.ResultsExposure of MIN6 cells to the ST extract (in concentrations that did not notably affect MIN6 cells: 5-15 mg/mL) was indeed able to minimize STZ-induced toxicity in MIN6 cells. Exposing macrophage-like RAW cells to ST extract (at 10-15 mg/mL) increased TNF-α gene expression, and this response was highly augmented by co-exposure to lipopolysaccharide (LPS, 1.0 mg/mL), indicating that ST extract contained inflammatory compounds too. The implication of this finding was investigated by exposing MIN6 cells to a subthreshold dose (100 ng/mL) of TNF-α, which 1) prevented the protective effect of the ST extract (10-15 mg/mL) against STZ toxicity, and 2) caused ST to become toxic to MIN6 cells even without the presence of STZ. TNF-α is known to activate the NF-κB pathway leading to cell death, however, NF-κB is also known to stimulate cell proliferation and survival. To investigate the relevance of the NF-κB pathway in our findings, we treated MIN6 cells with the proteasome inhibitor MG132 (at doses ≥0.2 μM), and observed that ST extract was no longer able to block STZ toxicity in MIN6 cells (p < 0.05), and to block CIAP2 expression, an anti-apoptotic target downstream from NF-κB.ConclusionThese data suggest that a leaf extract of ST has anti-diabetogenic efficacy, which may depend on the integrity of the NF-κB pathway. This protective effect appears to be impeded in a pro-inflammatory environment.